An integrated FEA-CFD simulation of offshore wind turbines with vibration control systems. (1st March 2022) - Kampitsis, Andreas; Kapasakalis, Konstantinos; Via-Estrem, Lluis
Abstract: The vibration mitigation of a monopile Offshore Wind Turbine (OWT) under wind and sea wave excitation is investigated, incorporating dynamic Vibration Control systems (VCS). The application of VCS to the OWTs has the potential to significantly improve the damping of the structure and its overall dynamic responses. A novel passive vibration absorption configuration is proposed, namely the Extended KDamper (EKD). Contrary to the conventional tuned mass dampers, EKD can increase its vibration absorption capability by introducing negative stiffness elements, instead of increasing the additional mass at the top of the towers. Therefore, EKD provides better isolation properties. The EKD optimum design and its realization are based on engineering criteria and realistic manufacturing limitations. The turbulence wind load time histories are determined stochastically while the mean velocity value is produced using the Blade Element Momentum theory. The influence of the sea wave excitation is studied using an integrated Computational Fluid Dynamics (CFD) approach. For the sea wave simulation, both fluids (water and air) are discretized using a non-uniform grid on which the Navier–Stokes equations are solved using the Double Control Volume Finite Element Method (DCVFEM). In order to render the large-scale physical problem computationally feasible, the Dynamic Adaptive Mesh Optimisation (DMO) and High Performance Computing (HPC) schemes are incorporated. The OWT tower is modelled using variable cross section beam elements accounting for geometrical nonlinearity (second order phenomena). The monopile soil–structure interaction (SSI) is modelled using a prismatic beam on elastic foundation together with the corresponding springs and dashpots along the pile's length. An extensive case study is carried out on a monopile OWT providing insight to the structural dynamics and illustrating the viability of the VCS on the offshore wind industry. It is shown that vibration control can extend the lifetime of the structure, increasing the OWTs' reliability and sustainability. Highlights: The Extended KDamper is proposed for passive vibration control of offshore wind turbines. Detailed design of the Extended KDamper is presented. Nonlinear FEA is carried out accounting for the combined action of wind and sea wave excitation. Computational Fluid Dynamics is used to extract the sea wave excitation. Soil–structure interaction is considered for a monopile foundation.